Tradisi Molonthalo di Gorontalo - M Gazali Rahman (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2012)
This paper explores the ritual of molonthalo, a Gorontalonese traditional ceremony. The molonthalo is performed regarding with the seventh or eighth of pregnancy. This ritual is aimed of express thankful and an expression ‘endowment’ searching by a person or group within the community who believe that there is a Supremy Being in their lives. This study uses an ethnography which is combined with socio-cultural, fenomenology, and normative. It has been found that the molonthalo ritual classied into ‘urf shahih dan ‘urf fasid. It is indicated that there is a relation between this ritual and Islamic tradition. Also there are a number of elements within the ritual are not compatible with the Islamic values. Therefore, a contructive reconstruct-totion to this tradition should be evaluated—that is aimed to Allah centris. Too, this tradition is initiated to prevent community from irrational magic, myths and animism.